A SYSTEMATIC REVIEW OF GRAPHIC ORGANIZERS METHOD IN READING COMPREHENSION - Emilia Elvi Santika; Finny Anita; Ageung Darajad (XXXX-XXXX, 2021)
This research aimed to review previous relevant studies to see the contribution of graphic organizers method in reading comprehension. This research was conducted using a systematic review qualitative research method. The object in this study were five previous relevant studies that have been selected using inclusion and exclusion criteria.  The method used to collect the data in this study were internet searching (Google Scholar), manual searching, and Zotero software. The data was analyzed by thematic analysis. The results of the review showed that overall the students’ achievement after applying graphic organizers had improved such as: (1) students more creative in make their own graphic organizers, (2) it help them to separate relevant details from what is fascinating but not necessary for instance, (3) store vocabulary, (4) summarize reading text, (5) students’ confidence had improved, (6) the knowledge of student’s text structure had improved and (7) deepen understanding. That’s mean graphic organizers gives such a positive contribution to the students in reading comprehension.